2006
DOI: 10.1002/clc.4960290911
|View full text |Cite
|
Sign up to set email alerts
|

Subaortic stenosis caused by left ventricular outflow tract lipoma

Abstract: (Fig. 1). Magnetic resonance imaging (MRI) was performed using electrocardiographic gating, and the oblique sagittal view revealed a lobulated-contoured soft tissue approximately 25 ϫ 40 ϫ 20 mm in the interventricular septum, protruding into the LVOT. The tumor, which showed high signal intensity compatible with fat tissue on time constant-weighted MR images, was determined to be a lipoma (Fig. 2).A 74-year-old man presented with palpitations and a systolic murmur over the aortic area. Transoesophageal echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Also, the dare issue with lipoma does not reside in its histological characteristics but its intracavitary component. Thus, the presence of cardiac lipoma becomes lethal when it occupies the LV cavity, resulting in obstruction and compression, which eventually causes peripheral embolism, LV failure, and rhythm and conduction disorders (12)(13)(14). The patient's symptoms in the presented case were those of heart failure with dyspnea and peripheral edemas.…”
Section: Discussionmentioning
confidence: 81%
“…Also, the dare issue with lipoma does not reside in its histological characteristics but its intracavitary component. Thus, the presence of cardiac lipoma becomes lethal when it occupies the LV cavity, resulting in obstruction and compression, which eventually causes peripheral embolism, LV failure, and rhythm and conduction disorders (12)(13)(14). The patient's symptoms in the presented case were those of heart failure with dyspnea and peripheral edemas.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the ages of the included patients ranged from 0.1-77.0 years, while the majority of patients (25/33) were aged ≥30.0 years. Most cardiac lipomas are asymptomatic and have a good prognosis; however, some giant cardiac lipomas can cause left ventricular inflow or outflow disturbances, left ventricular dysfunction or conduction system invasion ( 30 , 40 ). These conditions can induce dyspnea, presyncope, syncope or palpitations ( 30 , 40 ); however, the present study reported on a patient that presented with no etiologic chest pain, which could be considered as cardiac lipoma in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually incidentally-discovered during cardiac investigations that are performed for other reasons. Symptoms such as dyspnea, pre-syncope, syncope or palpitations can occur if the tumor grows and causes LV inflow or outflow obstruction, LV dysfunction or invasion of the conduction system [2,[5][6][7]. Sudden cardiac death has been reported, but the true incidence is unknown given the rarity of this cardiac tumor [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%